The Development of Augmented Reality Application to Explore Fluid Concepts - Handjoko Permana; Fauzi Bakri; Indah Hanifa Salsabila; Diah Ambarwulan; Dewi Muliyati; Dadan Sumardani (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2021)
Exploration can be done by reading, discussing, or experimenting with collecting and processing data. In fluid material, students can explore by looking at the phenomena related to the application of Archimedes' law, Pascal's law, and Bernoulli's law. This study aims to develop teaching materials that can improve students' ability to explore fluid material. The research method used is the 4D model development research. The study results were in marker applications and augmented reality, which was validated by material experts, learning media. This application has also gone through field trials. The validation value of material experts is 86%, and media experts are 82.5%. Meanwhile, the test results for the teacher obtained 83.75%, and the students obtained 83.45%. Based on the validation results, this media is feasible to be used as a learning medium that helps students improve fluid material.